1998
DOI: 10.1021/np9704664
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the Cytotoxicity of Lanostanoids and Steroids of Ganoderma tsugae through Apoptosis and Cell Cycle

Abstract: A new lanostanoid ester glucoside, 3 alpha-acetoxy-5 alpha-lanosta-8,24-dien-21-oic acid ester beta-d-glucoside (1), and a known steroid, 2 beta,3 alpha,9 alpha-trihydroxy-5 alpha-ergosta-7,22-diene (2), were isolated from the fruit bodies of Ganoderma tsugae and their structures determined by spectroscopic methods. To study the cytotoxicity of 1 and 2, the changes of DNA content in human hepatocytes (Hep 3B) were studied. A sub-G1 cell stage was drastically increased after 24-h incubation with 1 (24 microgram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 8 publications
1
60
0
1
Order By: Relevance
“…Traditionally, Ganoderma is highly regarded as a herbal treatment and is claimed to alleviate or cure virtually all diseases. Current research is focused on purification and characterization of the bioactive components and determination of their clinical value, especially their putative antitumor and anti-ageing properties (2,4,12,14,21). Many biologically active oxygenated lanostane-type triterpenoids have already been isolated from G. lucidum, and some of them have been shown to inhibit histamine release from rats mast cells (9,10) and angiotensin-converting enzyme (15).…”
mentioning
confidence: 99%
“…Traditionally, Ganoderma is highly regarded as a herbal treatment and is claimed to alleviate or cure virtually all diseases. Current research is focused on purification and characterization of the bioactive components and determination of their clinical value, especially their putative antitumor and anti-ageing properties (2,4,12,14,21). Many biologically active oxygenated lanostane-type triterpenoids have already been isolated from G. lucidum, and some of them have been shown to inhibit histamine release from rats mast cells (9,10) and angiotensin-converting enzyme (15).…”
mentioning
confidence: 99%
“…The majority of anticancer drugs in clinical use induce tumor cell apoptosis, via activating several apoptotic signaling pathways, including those of the mitochondria and endoplasmic reticulum. FPOA has previously been revealed to cause Hep 3B cell death by apoptosis (14). However, the apoptotic pathway induced by FPOA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Lucialdehyde c has been revealed to exert cytotoxic effects on Lewis lung carcinoma, T-47D, sarcoma 180 and meth-A tumor cell lines (13). Furthermore, 3-acetoxylanosta-8,24-dien-21-oic acid (FPOA), which was initially isolated from Ganoderma tsugae, has been identified to induce human hepatoma Hep3B cell death by apoptosis (14,15). With increasing research into triterpenoids, the mechanisms of their antitumor effects have been demonstrated to include induction of apoptosis, cell cycle inhibition and regulation of the immune response (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Pat. 1887 (24S)-24-Methyl-5α-cholest-7-ene-3β-ol and (24S)-24-Methyl-5α-cholest-7, l6-diene-3β-ol Strigina et al 1971 Alnusenone, Furanoganoderic acid, Friedelin, Ganoderenic acid F, Ganoderenic acid G, Ganoderic acid B8, 5,, Methyl ganoderenate H and Methyl ganoderenate AP Nishitoba et al 1989 Applanoxidic acid A and Applanoxidic acid B Tokuyama et al 1991Yoshikawa et al 2002 Applanoxidic acid F, Applanoxidic acid G, Applanoxidic acid H and Applanoxidic acid E Chairul & Hayashi 1994 24ξ-Methyl-5α-lanosta-25-one and Ergosta-4, 6, 8(14), 22-tetraen-3-one Gan et al 1998a Lucidone A, 24ξ-Methyl-5α-lanosta-25-one, Epidioxyergosta-6,9(11), 22-trien-3β-ol (9,11-Dehy-droergosterol peroxide), Ergosta-7, 22-dien-3-one and Ergosta-7, 22-dien-3β-yl palmitate Gan et al 1998b Ergosterol, Ganoderenic acid A, Ganoderenic acid D, β-Amyrenone, β-Amyrin acetate, Ganoderma aldehyde and 2, 5-Dihydroxy benzoic acid Ming et al 2002 Ergosterol; (24S) as C28 sterols from G. applanatum Cole & Schweikert 2003 Methyl ganoderenate D, 23-Dihydroganoderenic acid I, 11,15,methyl ester 3β,7β ,20,7β,20,11,11,20E (22)-dien-26-oic acid Shim et al 2004 D-mannitol, 2-methoxy fatty acids, cerebrosides, Daucosterol, 2, 5-Dihydroxyacetophenone, 2, 5-dihydro-xyacetophenone, 2,5-dihydroxybenzoic acid and Protocatechualdehyde Lee et al 2005 3α-Carboxyacetoxy-24-methylene-23-oxolanost-8-en-26-oic acid, 3α-Carboxyacetoxy-24-methyl-23-oxolanost-8-en-26-oic acid, 3α, 16α-Dihydroxylanosta-7,9(11),24-trien-21-oic acid, 16α-Hydroxy-3-oxolanosta-7,9(11), 24-trien-21-oic acid and 3α, 16α, 26-Trihydroxylanosta-7,9(11),24-trien-21-oic acid De Silva et al 2006 Ergosterol peroxide (5,8-epidioxy-5α-8α-ergosta-6,22E-dien-3-βol), 22E,24R-Ergosta-7,22-diene-3β,5α,6β-triol (Cerevisterol) Lee et al 2006 Methyl australate, 5α-ergost-7-en-3β-ol, 5α-ergost-7, 22-dien-3β-ol, 5, 8-epidioxy-5α, 8α-ergost-6, 22-dien-3β-ol, Methyl australate and Australic acid Smania et al 2007 Two laccase enzymes from G. australe Elissetche et al 2007 Fornicatin G (7β-hydroxy-11-oxo-3, 4-seco-25, 26, 27-trinorlanosta-4(28),8-dien-24-oic-3-acetyl ester) Fornicatin H Peng et al 2012 3β, 22S-Dih...…”
Section: G Annulare Lloyd) Boedijn 1940mentioning
confidence: 99%